Batas pemberian uang japuik dalam pernikahan adat Minangkabau menurut tokoh muhammadiyah dan nahdlatul ulama (Studi kasus pada masyarakat medan denai, kota Medan) - Salwa Nakita, Delvi; Hayati, Amal; Lubis, Zulpahmi (Universitas Islam Negeri Sumatera Utara Medan, 2025)
Abstract This study examines the limits of uang japuik in Minangkabau marriage traditions from the perspectives of Muhammadiyah and Nahdlatul Ulama, focusing on a case study of the Medan Denai community, Medan City. The tradition of uang japuik in Minangkabau marriages, particularly among the Pariaman community, remains widely practiced to this day, including in Medan Denai District. Uang japuik is understood as a form of appreciation given by the bride’s family to the groom. However, in practice, this tradition often gives rise to problems, especially regarding the amount of uang japuik, which may impose a financial burden on one of the parties. This research is a field study employing a comparative normative-empirical approach. Data analysis was conducted using both deductive and inductive methods by examining the views of Islamic scholars and religious organizations and contextualizing them with social practices, as well as by analyzing empirical phenomena in the field in relation to normative foundations. Data were collected through interviews with religious leaders, customary leaders, and members of the Minangkabau community in Medan Denai.The findings indicate that Muhammadiyah emphasizes the importance of reasonable limits in the provision of uang japuik to avoid burdening the bride’s family and to ensure compliance with Islamic legal principles. In contrast, Nahdlatul Ulama adopts a more flexible stance, viewing uang japuik as part of ‘urf (local custom) that is permissible as long as it is based on mutual deliberation and agreement, without stipulating a fixed nominal limit.